Peningkatan Pemahaman Pegawai Kecamatan Dolat Rayat Terkait Aplikasi CapCut Melalui Pendampingan Pembuatan Video Dokumentasi - Sembiring, Nita; Sinaga, Mikha Dayan; Manurung, Marlina; Sianturi, Charles Jhony Mantho; Ginting, Erwin (Publikasi Pengabdian Masyarakat, 2024)
The rapid development of information technology, especially in the field of multimedia, has changed the way we communicate and document various activities. The use of video as a means of documentation is now the main choice in conveying information, both in the personal sphere and government agencies. Dolat Rayat District, like many other districts, often carries out various activities and programs that involve the community. Some examples of activities that are often carried out include social events, community meetings, seminars, and infrastructure development projects. For the purpose of reporting and promoting these activities, good and easily accessible documentation is very important. The use of CapCut for making video documentation is very relevant because this application is available for free and easily accessible via mobile devices that are generally owned by district employees. In addition, the features in this application greatly support the creation of professional video documentation, although it does not require high video editing skills. However, most employees of Dolat Rayat District still do not master the techniques and understanding needed to make maximum use of this application. Through this assistance, it is hoped that there will also be an increase in employee capacity in utilizing technology to support their duties and responsibilities, as well as improving the quality of communication and reporting at the government level.